PENGARUH MEDIA GENIALLY TERHADAP MINAT BELAJAR SISWA PADA MATA PELAJARAN IPAS KELAS IV SEKOLAH DASAR MUHAMMADIYAH 12 PAMULANG - Dewi, Nurlina Arsita; Setiyaningsih, Dewi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
In writing this research is motivated by the low interest in learning science in grade IV students, so the author is moved to examine what causes the low interest in learning science, the alternative used in this study is to use animation media during the learning process. The purpose of this study is to determine the effect of using genially media on students' interest in learning science. This type of research is an experimental study with a quasi-experimental design, with the hypothesis that there is an effect of genially media on students' interest in learning science in grade IV students. The results of this study indicate that there is a significant effect of using genially media on interest in learning science in grade IV students. This is evident from the results of the calculation of the experimental class value of 82.07, and the class of the calculation of the control class value of 76.79. With the difference in the experimental class and the control class, namely 2.6 with a t-count of 2.608 and an F-count of 0.600 and also a significance value of 0.012 is smaller than 0.05 which means H0 is rejected and Ha is accepted.